2003
DOI: 10.1509/jmkr.40.3.249.19241
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Web Site Browsing Behavior Estimated on Clickstream Data

Abstract: Using the clickstream data recorded in Web server log files, the authors develop and estimate a model of the browsing behavior of visitors to a Web site. Two basic aspects of browsing behavior are examined: (1) the visitor's decisions to continue browsing (by submitting an additional page request) or to exit the site and (2) the length of time spent viewing each page. The authors propose a type II tobit model that captures both aspects of browsing behavior and handles the limitations of server log-file data. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
227
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(235 citation statements)
references
References 34 publications
7
227
0
1
Order By: Relevance
“…Web site designers should stay within the norms of other web site designs to ensure that these sites meet users ' expectations. 2 Research has found that ease of usability becomes strained when users are unfamiliar with the design or structure of a web site. 2,22 This is similar to Lutz and Kakkar ' s 25 fi nding that brick-and-mortar consumers who are overloaded with information and choices in the retail marketplace feel intimidated and often exit the environment.…”
Section: Structure (Ease Of Use)mentioning
confidence: 99%
See 3 more Smart Citations
“…Web site designers should stay within the norms of other web site designs to ensure that these sites meet users ' expectations. 2 Research has found that ease of usability becomes strained when users are unfamiliar with the design or structure of a web site. 2,22 This is similar to Lutz and Kakkar ' s 25 fi nding that brick-and-mortar consumers who are overloaded with information and choices in the retail marketplace feel intimidated and often exit the environment.…”
Section: Structure (Ease Of Use)mentioning
confidence: 99%
“…9,19 To improve web site ease of use, designers should strive to maintain lower numbers of pages needed to complete a task. 2 Additionally, web sites must have clearly distinguished links that inform the user of the destination. 20 Furthermore, Huber 19 calls for the importance of web site fl ow, and suggests effective use of headlines, photos and captions, and use of text on buttons to call for specifi c actions.…”
Section: Structure (Ease Of Use)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, they did find that more active shoppers tend to visit more sites. Bucklin and Sismeiro (2003) model online browsing behavior and find that with repeat visits to an online site, browsers view fewer pages within the site, but the time they spend viewing each page is unchanged. Moe (2003) uses clickstream data to identify online shoppers as buyers, searchers, browsers, or knowledge-builders based on characteristics of their site visit sessions, while Moe (2006) uses clickstream data to develop a two-stage model of the consumer decision process.…”
Section: Online Searchmentioning
confidence: 99%